Census of Population and Housing, 1990 (United States): Summary Tape File 3A ([Verlag nicht ermittelbar], 1993)
Summary Tape File 3A contains sample data weighted to represent the total population. The collection also contains 100-percent counts and unweighted sample counts for total persons and total housing units. Additional population and housing variables include age, ancestry, disability, citizenship, education, income, marital status, race, sex, travel time to work, rent, tenure, value of housing unit, number of vehicles, and monthly owner costs. The data for the states include 178 population tables and 99 housing tables. The information for Puerto Rico includes 149 population tables and 101 housing tables. Data are provided for states and Puerto Rico and their subareas in hierarchical sequence down to the block group level.